Implementation of Poluno Flashcard Learning Media in Environmental Pollution Material for Class X - Hartaji, Ezer Widhi; Tapilouw, Marisa Christina; Djohan, Djohan (Universitas Muhammadiyah Pontianak, 2025)
The study of biology offers students the opportunity to analyze environmental problems, including environmental pollution and its impact on ecosystem balance. This study aimed to develop flashcard learning media on water pollution sub-materials and to analyze their effectiveness in improving the understanding of grade X high school 1, Getasan, Semarang County Central Jawa. The research used the Research and Development (R & D) method, utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In the analysis stage, the need of flashcard use for water pollution learning was identified. As many as 47 flashcards of 6 topics were made in the design stage. The flashcard material aspect and media aspect were validated with scores of 89,4% dand 88,6% respectively in the development stage. The N-Gain score of 0,40 in the implementation stage implied medium level improvement of student learning outcomes. Finally, At the evaluation stage, it was found that teacher and student’s responses were very effective based on their responses as 84.4% and 82,6% respectively. Overall, the flashcards of environmental pollution learning were appropriate to be used for grade x high school students.